Direct adaptive equalization based on fast sparse recursive least squares algorithms for multiple-input multiple-output underwater acoustic communications - Qin, Zhen; Tao, Jun; Wang, Xiaoyan; Luo, Xinwei; Han, Xiao (The Journal of the Acoustical Society of America, 2019)
The sparse direct adaptive equalizer (DAE) has recently attracted much attention in underwater acoustic (UWA) communications for its improved performance compared with conventional non-sparse DAEs. The recursive least squares (RLS) type sparse DAEs were barely studied, mainly due to their high complexity despite fast convergence. This letter presents several low-complexity sparse RLS algorithms for multiple-input multiple-output UWA channel equalization. The resulting fast sparse RLS DAEs are tested to be effective and outperform their non-sparse counterpart by experimental results.